PENGARUH SURAT TEGURAN DAN SURAT PAKSA TERHADAP PELUNASAN TUNGGAKAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA KOLAKA - Arman, Arman (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACTThis study aims to determine the effect of the warning letter and the letter of forced against the settlement of tax arrears to the Tax Office Pratama Kolaka. Methods of data analysis used in this research is multiple linear regression analysis to examine and provide an overview of how the influence of the warning letter and the letter of forced against the settlement of tax arrears for 2010-2014 on the Tax Office Pratama KolakaBased on the results of data analysis using SPSS 21 indicates that the results of partial hypothesis test (t-test) proves that the warning letter was not positive and not significant to the repayment of tax arrears. tcount <ttable is -0.035 <1.740 with a significant level of 0.972> 0.05. The results of partial hypothesis test Â (t-test) proves that the letter forced positive and significant effect on the repayment of tax arrears. tcount> ttable namely 2.794> 1.740 with significant level of 0.012 <0.05. Hypothesis test results simultaneously ((F-test) proves that the warning letter and the letter forced a significant effect on the repayment of tax arrears. The coefficient of determination shows 0.319 or 31.9%, which means 31.9% repayment of tax arrears is affected by the number of warning letters and letters forced published. the remaining 68.1% is influenced by other factors not discussed in this study.Â Keywords: Warning Letter, Letter Forced and Tax Arrears Settlement